2018
DOI: 10.1017/jpa.2018.71
|View full text |Cite
|
Sign up to set email alerts
|

An orb-weaver spider (Araneae, Araneidae) from the early Eocene of India

Abstract: A new fossil spider is described from the early Eocene (Ypresian) Palana Formation (54 to 57 Ma) at the Gurha opencast lignite mine, near Bikaner, western Rajasthan, India. It is the first report of a nonamber fossil spider from India. The fossil is referred to the modern genusNephilaLeach, 1815, but with hesitation because, while its habitus is similar to that genus, it lacks the behavioral synapomorphies that distinguish the genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Shukla et al (2014) already indicated the presence of insects from this mine. Patel et al (2019a) recently described an orb-weaver spider (Araneae, Araneidae) and report only insects like Formica sp., mayfly naiad, etc. (Patel et al, 2019b) from the same formation, otherwise known for their fossil pollen, leaves, flowers, fruits, (Shukla et al, 2014;Shukla & Mehrotra, 2019).…”
mentioning
confidence: 99%
“…Shukla et al (2014) already indicated the presence of insects from this mine. Patel et al (2019a) recently described an orb-weaver spider (Araneae, Araneidae) and report only insects like Formica sp., mayfly naiad, etc. (Patel et al, 2019b) from the same formation, otherwise known for their fossil pollen, leaves, flowers, fruits, (Shukla et al, 2014;Shukla & Mehrotra, 2019).…”
mentioning
confidence: 99%